MULTIMEDIA INTERAKTIF BERBASIS KARAKTER SEBAGAI UPAYA MENINGKATKAN PEMAHAMAN NILAI-NILAI PANCASILA DAN JIWA NASIONALISME MAHASISWA STKIP MUHAMMADIYAH MUARA BUNGO - Arisman Sabir; Ikhsan Maulana Putra (LPPM Universitas Muhammadiyah Muara Bungo, 2021)
Pancasila is the basis of the state that becomes a guideline for people to behave and run well, in accordance with the ancestral culture of the Indonesian nation. The problem with this research is that students gradually forget the noble values ​​that characterize the Indonesian nation. The purpose of this study resulted in the development of Interactive Multimedia that was suitable for use in PKN learning material on Pancasila values and nationalism. The expected solution for developing interactive multimedia products is in the form of software applications containing material for Pancasila values and nationalism which are packaged in Compact Disc form or can be stored on a flash disk so that the product is more flexible for students to use. This study uses a development method by applying the ADDIE procedure, namely: media analysis, material, character values. Based on the results of the research, the results of interactive multimedia based on character and nationalism meet the very valid criteria with the results of the media expert test reaching 93%, the material expert achieving the validity level of 87%, the linguist reaching 87%, and the field trial results reaching 86.9%, p. This is because the material values ​​​​of Pancasila and nationalism have color compatibility, image compatibility, writing size suitability, typeface suitability, attractive cover design, able to provide convenience. The results of student understanding mean the pre-test score is 61.5 and the post-test score is 85.5. In the manual t-test with a significance level of 0.05, the results of tcount 3.535 6> ttable2.093 means Ho is rejected and Ha is accepted. There is a significant difference in the material of Pancasila values ​​and nationalism developed, so that character-based interactive multimedia is appropriate to be used in civic education learning as a source and material for civics learning at STKIP Muhammadiyah Muara Bungo.